EFFICIENCY OF ELECTRONIC EDUCATIONAL RESOURCES FOR THE IMPLEMENTATION OF DISTANCE LEARNING OF STUDENTS WITH SPECIAL EDUCATIONAL NEEDS (ON THE EXAMPLE OF LMS MOODLE AND MICROSOFT TEAMS) - Хомік, Оксана; Savchuk, Nadiia (Educological discourse, 2021)
The article considers ways to expand the availability of higher education for students with special educational needs. The introduction of European principles and standards in the field of education is an important step towards the implementation of the model of inclusive education in our country. The importance of distance learning as one of the available forms of education for students with disabilities in higher education institutions of Ukraine is emphasized. Information and communication technologies can be a powerful tool to support education for people with disabilities. Monitoring of students with disabilities was carried out to determine their needs in the process of obtaining higher education. The main difficulties that students with different nosologies overcome in the process of studying in higher education institutions are identified. One of the ways to improve the training of students with disabilities in modern higher education is the introduction of distance learning using electronic educational services, including platforms Moodle and Microsoft Teams. The main features and benefits of the distance course "Psychology of Health and Healthy Lifestyle", created in the Moodle system, are described. However, the disadvantage of using the Moodle platform to teach students with disabilities is the lack of personal communication with group members, which is very important when teaching students with disabilities. The differences and advantages of the Microsoft Teams service over the Moodle platform in the process of distance learning of students with special educational needs are considered. Microsoft Teams offers technologies for clear audio and video transmission, data exchange, and the organization of separate sessions for collaborative and individualized learning that simplify the learning process. The process is presented of organizing a distance course "Psychology of Health and Healthy Lifestyle" to conduct classes with students with special educational needs on the platform Microsoft Teams and emphasizes the feasibility of its implementation in higher education